KARAKTERISTIK MINYAK SEREH WANGI DARI DAERAH ISTIMEWA YOGYAKARTA - Woesono, Hastanto Bowo; Sushardi; Purwanto, Muhammad Amir (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2021)
The market needs will be fragrant citronella oil increases, but it is not worth the production and quality of fragrant Lemongrass oil is produced. The purpose of this study, that is, to figure out the best combination of sources of raw materials and factors of the size of the craftmanship the leaves against the yield and quality of fragrant citronella oil. Research design used was Random Complete Factorial Design, using two combination treatment that is the source of the raw material and the size of the craftmanship leaves. The observed parameters include: color, yield, citronellal, citronellol and geraniol. The results of this study indicate that the color of the resulting eligible SNI 06-3953-1995 that is pale yellow to yellow-brown. Combination treatment of the source of the raw material and the size of the leaf is very different from real craftmanship against yield oil of citronella scented with the highest average on the source of raw material for the village of Wedomartani, craftmanship and size of 0.93% leaves 10 cm that is 0.94%. Chemical content of citronellal shows that the source of the raw material and the size of the different leaf craftmanship not real. Chemical content of citronellol and of the raw materials sources that geraniol very different real, whereas the size of different leaf craftmanship not real. The average content of chemical sitronellol and geraniol at the source of the raw materials of the highest village of Kebonharjo, the content of citronellol 13.11% and geraniol content 34.84%. Key words: raw material sources, treatment, quality of citronella oils